Language development, hearing loss, and intracranial hypertension in children with TWIST1-confirmed Saethre-Chotzen syndrome - Kilcoyne, S; Luscombe, C; Scully, P; Jayamohan, J; Magdum, S; Wall, S; Johnson, D; Wilkie, AOM (Lippincott, Williams and Wilkins, 2019)
Saethre-Chotzen syndrome (SCS) is an autosomal dominant condition defined by mutations affecting the TWIST1 gene on chromosome 7p21.1. Previous research has identified an elevated prevalence of intracranial hypertension and hearing impairment associated with this syndrome. This study aimed to investigate the influence of hearing history and presence of intracranial hypertension on language development in children with SCS. A retrospective study note analysis was performed for all patients with a confirmed TWIST1 gene abnormality who attended the Oxford Craniofacial Unit and underwent a language assessment over a 22-year period. Intracranial pressure monitoring, hearing status, and language outcomes were examined in detail. Thirty patients with genetically confirmed SCS and language assessment data were identified. Twenty-eight patients underwent surgical intervention; 10 presented with intracranial hypertension (5 prior to, and 5 after primary surgical intervention). Language data coinciding with the presentation of intracranial hypertension were available for 8 children. About 44% of children with intracranial hypertension presented with concurrent receptive and expressive language delay (n = 4/8). For both children (n = 2) with longitudinal language data available, the onset of intracranial hypertension reflected a concurrent decline in language skills. Audiometric data were available for 25 children, 80% (n = 20/25) had a history of hearing loss. About 50% of these had confirmed conductive hearing loss with middle ear effusion and the other 50% had presumed conductive hearing loss with middle ear effusion. About 100% of the children with available hearing data in our study had evidence of middle ear effusion in at least 1 ear. Results also indicated that 43% (n = 13/30) of the children presented with receptive and/or expressive language delay during childhood. Given the importance of hearing for language development and the preliminary findings of a potential decline in language skills in children during periods of intracranial hypertension, regular follow-up of hearing, language, and intracranial hypertension are indicated in children with SCS.